Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages Foremost among the new features we would emphasise the following:— The unification of all Local Services under a Ministry of Social Security and the fixing of benefits on the basis of definite subsistence scale, the various items of which can be tested in relation to their adequacy and their cost to workers, employers, and State. The criticism that this would mean an increase of bureaucracy and red tape is not justified. It is the division of responsibility for the Social Services between the Government and the local authorities and between various Government departments that gives scope for delays, red tape, and the shifting of responsibility. The unification of the Social Services under a single Ministry, working on one set of agreed principles, will mean a tremendous simplification of administration, and the speedier settlement of claims. The proposal for the National Medical Service which would give the insured contributors and their dependants whatever treatment their case requires "at home, or in an institution - medical, dental or subsidiary - without a treatment charge." When we compare this with the present state of affairs, where workers are often unable to get hospital treatment until their ailment has reached a stage where there would be danger to their life if it were not treated, we can see that this is a vast improvement. The abolition of separate approved societies, the majority of which are annexes of the profit-making insurance companies and are administered by agents who mix approved society and insurance business, is long overdue. The insurance companies' charge that 8 15X/2/103/272